Oficinas terapêuticas com mulheres vítimas de violência sexual: atendimento a refugiadas africanas - Érica Toledo Corrêa (2024)
This experience report concerns the holding of therapeutic workshops with African refugee women, victims of sexual abuse. The objective of the work was to develop a care methodology for this type of problem. The workshops were planned and conducted based on the Psychoanalytic Theory and combined three therapeutic dimensions: discursive, narrative and corporal. In discursive practices of personal reports, the relevance of testimony to alleviate the pain of invisibility was observed. Using the narrative tools, symbolic resources were offered to expand the repertoire of trauma elaboration. And with the use of the dance, we sought to integrate what cannot be achieved by words, translating part of the unconscious contents into movements. The application indicated positive results and the African women's experience with their own bodies revealed some protective aspects of subjectivity in the face of sexual violence. Such findings suggest a valuable path forward in providing care to the Brazilian women.